Comparative transcriptome analysis identifies candidate genes related to seed coat color in rapeseed - Guan, Mingwei; Shi, Xiangtian; Chen, Si; Wan, Yuanyuan; Tang, Yunshan; Zhao, Tian; Gao, Lei; Sun, Fujun; Yin, Nengwen; Zhao, Huiyan; Lu, Kun; Li, Jiana; et al. (Frontiers in Plant Science, 2023)
Yellow seed coat in rapeseed (Brassica napus) is a desirable trait that can be targeted to improve the quality of this oilseed crop. To better understand the inheritance mechanism of the yellow-seeded trait, we performed transcriptome profiling of developing seeds in yellow- and black-seeded rapeseed with different backgrounds. The differentially expressed genes (DEGs) during seed development showed significant characteristics, these genes were mainly enriched for the Gene Ontology (GO) terms carbohydrate metabolic process, lipid metabolic process, photosynthesis, and embryo development. Moreover, 1206 and 276 DEGs, which represent candidates to be involved in seed coat color, were identified between yellow- and black-seeded rapeseed during the middle and late stages of seed development, respectively. Based on gene annotation, GO enrichment analysis, and protein–protein interaction network analysis, the downregulated DEGs were primarily enriched for the phenylpropanoid and flavonoid biosynthesis pathways. Notably, 25 transcription factors (TFs) involved in regulating flavonoid biosynthesis pathway, including known (e.g., KNAT7, NAC2, TTG2 and STK) and predicted TFs (e.g., C2H2-like, bZIP44, SHP1, and GBF6), were identified using integrated gene regulatory network (iGRN) and weight gene co-expression networks analysis (WGCNA). These candidate TF genes had differential expression profiles between yellow- and black-seeded rapeseed, suggesting they might function in seed color formation by regulating genes in the flavonoid biosynthesis pathway. Thus, our results provide in-depth insights that facilitate the exploration of candidate gene function in seed development. In addition, our data lay the foundation for revealing the roles of genes involved in the yellow-seeded trait in rapeseed.